Functional annotation of selected streptococcus pneumoniae hypothetical proteins - Razali, Khairiah; Abdul Hamid, Azzmer Azzar; Md Zin, Noor Hasniza; Muhamad Bunnori, Noraslinda; Ahmad Yusof @ Hanafi, Hanani; Kamarudin, Kamarul Rahim; Mohamed Rehan, Aisyah (Universiti Sains Islam Malaysia, 2019)
The ability of Streptococcus pneumoniae to induce infection relies on its virulence factor machinery. A previous study has identified essential proteins that might be responsible towards the pathogenicity of S. pneumoniae serotype 2 strain D39. How ever, 39 of them were yet functionally and stru cturally uncharacterized. Thus, by using in silico approach, this study aims to annotate the function and the structure of these unannotated proteins. Initially, all 39 targeted proteins went through primary screening for template availability and pathogen icity. From there, 11 of them were selected and were further analyzed on the basis of their physicochemical, functional and structural categorization using an integrated bioinformatics approach by means of amino acid sequence and stru cture - based analysi s. The obtained data suggested that all targeted proteins showed high possibility to be involved in either cell viability or cell pathogenicity mechanism of the bacterium, with SPD_1333 and SPD_1743 being the two most promising proteins to be further studied. Findings from this study could provide a better understanding of the pathogenic ability of this microorganism and thus, enhance drug development and target identification processes in the aim of improving pneumococcal disease control.